Factors influencing fecundity in experimental crosses of water lotus (Nelumbo nucifera Gaertn.) cultivars - Teng, Nian-Jun (BioMed Central, 2012)
BACKGROUND: Breeding programs for the water lotus (Nelumbo nucifera) are hampered by an inability to account for variation in seed set associated with crosses between different cultivars. We studied seed set in two reciprocal crosses between lotus cultivars (‘Guili’ × ‘Aijiangnan’ and ‘Molingqiuse’ × ‘Qinhuaiyanzhi') to obtain insights into factors that govern fecundity in these experimental hybrids. Pollen viability, stigma receptivity and embryo development were compared for each hybrid and reciprocal cross. RESULTS: Pollen viability of the individual cultivars ranged from 4.1% to 20.2%, with the highest level (>11.9%) for all cultivars observed from the earliest collected grains (05:00–06:00 a.m.). Stigmatic pollen germination peaked at 4 h after pollination and varied from 4.8 to 60.6 grains per stigma among the crosses. Production of normal embryos ranged from 7.6% to 58.8% at 1 d after pollination and from 0 to 25% by 11 d after pollination. Seed set in crosses (0.2–23.3%) was generally lower than in open-pollinated plants (8.4–26.5%). Similar to the germination results, seed set was substantially reduced in both reciprocal crosses. CONCLUSIONS: These results suggested that poor pollen fertility, low stigma receptivity, and embryo abortion were responsible for the failure of the crosses ‘Molingqiuse’ × ‘Qinhuaiyanzhi’, ‘Qinhuaiyanzhi’ × ‘Molingqiuse’, and ‘Aijiangnan’ × ‘Guili’.